ANALISIS KONTRIBUSI SUMBER PENDAPATAN ASLI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA SAMARINDA (Studi Kasus Pada Bapenda Kota Samarinda) - Lewi Patabang; Rahmawati Fitriana; Yongky Weldy (Politeknik Negeri Samarinda, 2019)
This study discusses which sources of Original local Government Revenues make the largest contribution to the Original local Government Revenues of Samarinda City. The method used in this study is a quantitative method, which is contribution analysis. This research data was obtained from the Regional Income Agency of Samarinda City. The results of the current study of Original local Government Revenues sources for 2014-2018 which contributed to a good assessment were the regional tax in 2018 which amounted to 70,72% which was supported by the contribution of Roadway Lighting Tax by 30,18% and lower contribution was in 2014 amounted to 54,77%. Keywords: Contributions, Source Original local Government Revenues.